2021
DOI: 10.1177/01655515211027789
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the public’s information behaviour preferences in multiple emergency events

Abstract: Due to the frequent occurrence of public emergency events and the extensive use of social media in recent years, the public is more and more involved in the communication of public emergencies. As important members of the public, the rapid and massive information sharing of social media users makes them play an increasingly crucial role in the emergency processing. Hence, it is necessary to analyse information behaviours of social media users in emergency events. This article mined the information behaviours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…They found that the number of offline press reports relating to the event published on the day the tweet is posted is a significant predictor of size [7]. Zhou mined the users' behaviors in four emergency events from microblogs to reveal their behavior preferences, and found that users' behaviors in emergencies are related to their own interests and economic status [8]. Some studies explored the communication dynamics in social networks/media during or after natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the number of offline press reports relating to the event published on the day the tweet is posted is a significant predictor of size [7]. Zhou mined the users' behaviors in four emergency events from microblogs to reveal their behavior preferences, and found that users' behaviors in emergencies are related to their own interests and economic status [8]. Some studies explored the communication dynamics in social networks/media during or after natural disasters.…”
Section: Introductionmentioning
confidence: 99%